FINANCIAL PERFORMANCE ANALYSIS KUPANG CITY REGIONAL GOVERNMENT - Sri Endar Utami; Agusta Amanda Wulandari; Tiffany NP Gah (SEAN Institute, 2023)
Maintenance government area based with principle autonomy area. Maintenance government areas are also marked with it changed system centralization become directed decentralization For speed up realization well-being Indonesian society. So from That every area sued For more independent in organize and manage affairs his government , incl in manage finance area. One deep vital cycle management finance area that is reporting carried out every end period accounting , in form report finance government regional (LKPD). LKPD can utilized as means in do analysis performance so that can increase role report finance That yourself . Therefore that , writer will do study more in For know performance Kupang City Regional Government for 5 years last . Study This use approach descriptive quantitative . The data collection method will be done with documentation . the data form Report Realization Budget contained in the 2018-2022 BPK Audit Results Report . the data Then analyzed use analysis ratio finance form ratio independence finance area ,ratio dependency finance area , ratio degrees decentralization , ratio effectiveness income original area , ratio efficiency finance area , ratio harmony and ratio growth . Research results state that role government center more dominant in finance maintenance government Kupang City area , dependency finance government area to center form transfer income for 5 years last very high , percentage income original area not enough If compared to with the entire total revenue , effectiveness income original area for 5 years final Enough effective . government area requires sufficient funds big even up every year during For finance operational government However capital expenditure is increasing decrease every the year . On the other hand , growth income from 2018 until with 2022 likely down , meanwhile growth shopping fluctuating operational and capital expenditures for 5 years last Therefore That Kupang City Regional Government expected can maximizing potency acceptance in the area . That thing To use reduce dominant government center in finance maintenance Kupang City Regional Government .